2019
DOI: 10.1080/09613218.2019.1630245
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying energy demand reduction considering householder willingness to apply measures

Abstract: Reducing energy demand in the domestic sector will be an important feature of future energy systems but is challenging to achieve in practice. Solutions lie in a range of building fabric and system improvements as well as adopting more sustainable routines and conceptions of normality in the home. The impact of such measures has so far been quantified without considering the willingness of the householder to adopt them. This paper uses a modelling approach to evaluate the effectiveness of technical and lifesty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…To address the urgent challenges associated with climate change and the move towards a low carbon society, changing energy demand has the capacity to support not only reductions in greenhouse gas emissions but also other key energy policy goals such as security and affordability (IPCC, 2018). The residential sector is reported to account for 27% of global energy consumption and 17% of CO2 emissions (Nejat et al, 2015), with considerable potential for emission reductions through rapid uptake of domestic solutions (Cosar-Jorda et al, 2019;Kesicki, 2012). Established techniques for helping reduce energy use in residential buildings include attic insulation, sealing drafts and double-glazed windows (Watson, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To address the urgent challenges associated with climate change and the move towards a low carbon society, changing energy demand has the capacity to support not only reductions in greenhouse gas emissions but also other key energy policy goals such as security and affordability (IPCC, 2018). The residential sector is reported to account for 27% of global energy consumption and 17% of CO2 emissions (Nejat et al, 2015), with considerable potential for emission reductions through rapid uptake of domestic solutions (Cosar-Jorda et al, 2019;Kesicki, 2012). Established techniques for helping reduce energy use in residential buildings include attic insulation, sealing drafts and double-glazed windows (Watson, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…• Provide 'added value' for those who are already 'engaged' but want to do more. For example, Cosar-Jorda et al [36] have demonstrated how personalised data could be used to inform householder decision making beyond retrofit.…”
Section: • Helps To Give People a Clear Idea Of How Much Energy They Use And Points Out Area's That Haven't Been Thought Aboutmentioning
confidence: 99%